Why Is There So Much More Research on Vision Than on Any Other Sensory Modality? - Hutmacher, Fabian (Frontiers in Psychology, 2019)
Why is there so much more research on vision than on any other sensory modality? There is a seemingly easy answer to this question: It is because vision is our most important and most complex sense. Although there are arguments in favor of this explanation, it can be challenged in two ways: by showing that the arguments regarding the importance and complexity of vision are debatable and by demonstrating that there are other aspects that need to be taken into account. Here, I argue that the explanation is debatable, as there are various ways of defining “importance” and “complexity” and, as considering these different definitions proves, there is no clear consensus that vision is indeed the most important and most complex of our senses. Hence, I propose two additional explanations: According to the methodological-structural explanation, there is more research on vision because the available, present-day technology is better suited for studying vision than for studying other modalities – an advantage which most likely is the result of an initial bias towards vision, which reinforces itself. Possible reasons for such an initial bias are discussed. The cultural explanation emphasizes that the dominance of the visual is not an unchangeable constant, but rather the result of the way our societies are designed and thus heavily influenced by human decision-making. As it turns out, there is no universal hierarchy of the senses, but great historical and cross-cultural variation. Realizing that the dominance of the visual is socially and culturally reinforced and not simply a law of nature, gives us the opportunity to take a step back and to think about the kind of sensory environments we want to create and about the kind of theories that need to be developed in research.